Association of dietary inflammatory index and vigorous physical activity on phenotypic age acceleration: a cross-sectional study with machine learning - Li, Shuoqi; Zhou, Jianming; Zhang, Dandan; Du, Qiuyu (Frontiers in Nutrition, 2025)
BackgroundDiet and inflammation are intricately correlated to the aging process. Diet has also been hypothesized to influence aging by regulating inflammation. The phenotypic age acceleration (PhenoAgeAccel) reflects the difference between an individual’s phenotypic and chronological age; a positive value suggests accelerated aging, whereas a negative value indicates slower biological aging. Accordingly, this study investigated the independent and comprehensive influences of vigorous-intensity exercises (VPA) and dietary inflammatory index (DII) on the PhenoAgeAccel in American adults.MethodsThe study enrolled 4,167 adults sourced from the National Health and Nutrition Examination Survey (NHANES) from 2007–2010 to 2015–2018. The NHANES is designed with a sophisticated, multistage probability sampling methodology and is specifically tailored to comprehensively assess the health and nutritional conditions of the non-institutionalized population. Five machine learning models were constructed to predict participants’ PhenoAgeAccel.ResultsThe PhenoAgeAccel of participants in Groups 3 (anti-inflammatory diet + insufficient VPA) and 4 (anti-inflammatory diet + sufficient VPA) were −2.72 (95% CI − 3.44, −1.93; p < 0.001), and −1.61 (95% CI − 2.65, −0.63; p < 0.001), respectively, when compared to the participants under 60 years old in Group 1 (pro-inflammatory diet + insufficient VPA). Conversely, a significantly increased PhenoAgeAccel was exhibited by Group 2 (pro-inflammatory diet + sufficient VPA), recording 0.81 (multivariable-adjusted β, 95% CI 0.13–1.75, and p < 0.01).ConclusionLow levels of VPA and anti-inflammatory diet consumption were associated with reduced biological aging. Anti-inflammatory diets can also aid in counteracting the harmful effects of significant levels of VPA on biological aging.